Retention of deuterium in beryllium: A combined investigation using TDS, ERDA and EBS. (October 2022) - Cupak, C.; Pitthan, E.; Moro, M.V.; Fellinger, M.; Primetzhofer, D.; Aumayr, F.
Abstract: We have studied the retention of deuterium in beryllium, implanted with an energy of 500 eV/D, using a combination of thermal desorption spectroscopy, elastic recoil detection analysis and elastic backscattering spectroscopy. The parallel use of these techniques allowed us to directly quantify the absolute deuterium content reduction of the sample for specific desorption peaks observed during thermal annealing. In addition, the presence of a beryllium oxide surface layer was observed, despite sputter-cleaning of the sample was initially conducted in-situ . A main result was that ∼ 85 % of the retained deuterium got released during the primary desorption peak at 400 K. A smaller, secondary desorption peak was identified at 540 K. All deuterium could be removed from the Be sample by heating it to a temperature of 800 K. Highlights: Deuterium retention in saturated beryllium studied for 500 eV/D irradiation. Parallel temperature desorption spectroscopy and ion beam analysis achieved in-situ. 85% of deuterium is released at primary desorption peak at 400 K. BeO formation during implantation was observed in UHV conditions.